Analysis of extracorporeal shock-wave lithotripsy in renal calcular disease among children: a tertiary care experience - Khan, Suhail M.; Khan, Azhar A.; Kanth, Anzeen N.; Khan, Aymen M.; Kanth, Irtifa N. (International Surgery Journal, 2021)
Background: The aim of this study is to review 10 years of extracorporeal shock wave lithotripsy (ESWL) experience in paediatric urolithiasis patients. Methods: Data from a cohort of paediatric urolithiasis patients who underwent shock wave lithotripsy between 2012 and 2019 at department of urology, Indraprastha Apollo, New Delhi were used in a single-centre, retrospective comparative study. During a seven-year period, 250 paediatric patients (Male/female: 134/116, mean age: 10.22 years, range: 1-18) had 284 shock wave sessions in our hospital, with 208 having primary and 42 having recurrent urolithiasis. A total of 328 stones were discovered, with 192 (58.5%) in boys and 136 (41.5%) in girls. For ample stone fragmentation, one session of 200 to 3000 shockwave impulses was required, though some patients required more than 8000 impulses over 4 sessions. However, in most patients, low-energy shockwaves with a frequency of 1-2 were used to fragment the stones. Results: Younger age was associated with quicker stone clearance in our study, which was likely due to shorter urinary tracts and a smaller "barrier" between the device and the stone. Furthermore, children who had renal colic prior to lithotripsy had a considerably lower chance of removing stones within two days than those who did not. This can be explained by the colic's underlying mechanism, which evolves against the backdrop of ureteric wall spasm. Mild macrohematuria and "steinstrasse" were identified in almost all patients during the first post-lithotripsy days, as predicted during the post-op course. There were no major obstructive, infectious, or other severe complications. Conclusions: Extracorporeal shock wave lithotripsy proved to be a safe and highly effective minimally invasive treatment of children with kidney stone disease.